43. IMPROVING THE MOTION RANGE WITH GALANTAMINE HYDROTHERAPY COMBINED WITH ELECTROACUPUNCTURE AND “THÂN THỐNG TRỤC Ứ THANG” IN THE TREATMENT OF SCIATICA DUE TO LUMBAR DISC HERNIATION (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the effects of Galantamine hydrotherapy combined with electroacupuncture and the herbal remedy “Thân thống trục ứ thang” in the treatment of sciatica (SCI) caused by lumbar disc herniation (LDH).Subjects and Methods: A prospective, open-label, controlled clinical trial at the Department of Traditional Medicine, Đống Đa General Hospital, from October 2022 to October 2023. The patients were divided into two groups: the research group received electroacupuncture, Galantamine hydrotherapy, and “Thân thống trục ứ thang” herbal remedy; the control group received electroacupuncture and “Thân thống trục ứ thang” herbal remedy. The treatment regimen had lasted for 15 consecutive days.Results: After 15 days of treatment, the patients in the research group showed significant improvement in clinical indicators compared to ones in the control group. Pain evaluated by VAS scale decreased significantly, the lumbar spinal flexibility index (Schӧber) and Lasègue’s sign index were both increased, and the range of motion in lumbar spinal movements (flexion, extension, lateral bending, and rotation) improved significantly. The daily living function index increased considerably, and sensory symptoms (numbness) were reduced more in treatment group than in the control group. The overall treatment outcomes indicated a significantly higher rate of good and fair responses in the research group compared to the control group. Adverse effects such as localized pain post-injection, headache, dizziness, and nausea were minor and resolved within a few days.Conclusion: Combining Galantamine hydrotherapy, electroacupuncture, and the herbal remedy "Thân thống trục ứ thang" in treating SCI caused by LDH showed high efficacy, significantly improves clinical indicators and daily living functions, with minor adverse effects that resolve on their own within a few days.
Keywords: Sciatica, disc herniation, hydrotherapy, Galantamine, electroacupuncture, “Thân thống trục ứ thang”, lumbar spine.